2013
DOI: 10.1523/jneurosci.3874-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Modes of Phase Locking between Sniffing and Whisking during Active Exploration

Abstract: Sense organs are often actively controlled by motor processes and such active sensing profoundly shapes the timing of sensory information flow. The temporal coordination between different active sensing processes is less well understood but is essential for multisensory integration, coordination between brain regions, and energetically optimal sampling strategies. Here we studied the coordination between sniffing and whisking, the motor processes in rodents that control the acquisition of smell and touch infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 59 publications
9
58
0
Order By: Relevance
“…Concurrent measurements of breathing and whisking in head-restrained rats reveal key aspects of their coordination (Moore and Deschênes et al 2013; Ranade et al 2013), and extend Welker’s initial descriptions (Fig. 3).…”
supporting
confidence: 78%
“…Concurrent measurements of breathing and whisking in head-restrained rats reveal key aspects of their coordination (Moore and Deschênes et al 2013; Ranade et al 2013), and extend Welker’s initial descriptions (Fig. 3).…”
supporting
confidence: 78%
“…These behaviors involve the use of common muscles in the snout 4, 17 , and their robust one-to-one coordination suggested that they might depend on a common rhythm generator. Since Welker’s initial qualitative observations, synchronous sniffing and whisking has been more completely described 18, 19 and quantified 20, 21 in a number of subsequent studies in rats. There is also evidence that high-frequency sniffing and whisking are phase locked in mice 20 ; however, one study reports a lack of such coordination in this species 22 .…”
Section: Coordination Of Orofacial Behaviors With Breathingmentioning
confidence: 99%
“…This proximity is likely to be functionally relevant since whisking is tightly coupled to fast breathing, typically called sniffing. Yet even fast whisking is gated separately from breathing (Welker, 1964; Moore et al, 2013; Ranade et al, 2013). The vibrissa-related region of the IRt (vIRt) contains facial premotor neurons and neurons that fire either in phase or in antiphase with vibrissa protraction.…”
Section: Introductionmentioning
confidence: 99%